Influence of Cd0.99Eu0.01SiO3 nanoparticles concentration on Cd0.99Eu0.01SiO3/PVDF nanocomposite films. (2018) - Shireesha, G.; Manjunatha, C.; Jain, Anjana; Radhakrishna, M.C.
Abstract: Nanocomposites of piezoelectric PVDF doped with Cd0.99 Eu0.01 SiO3 of varying concentration was prepared by spin coating technique. The prepared nanocomposites were investigated by X-ray diffraction technique and it showed an α to β transformation compared to pristine PVDF. This phase exhibits piezoelectric property employed in the design of Sensors and Actuators. SEM micrographs indicated a modification in surface morphology of the nanocomposites. Results of EDX indicate the incorporation of the elements of the nanodopant in PVDF. Differential Scanning Calorimetry showed an increase in degree of crystallinity. Optical bandgap energy of the nanocomposites increased with increase in concentration of nanodopant. Dielectric studies showed an enhancement in Dielectric permittivity and AC conductivity of the nanocomposites which can be employed in the design of energy storage devices